Carbon-based material reinforced interpenetrating network conductive hydrogel as well as preparation and application thereof

By using carbon-based materials to enhance interpenetrating network structure in conductive hydrogels, the problem of insufficient interaction between conductive materials and gel network interface is solved, significantly improving its mechanical properties and cyclic stability, and achieving weakening of human body Efficient monitoring of motion signals.

CN119119385AInactive Publication Date: 2024-12-13LANZHOU UNIVERSITY OF TECHNOLOGY

Patent Information

Application Number
CN202411297055.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The interface interaction between the conductive material and the gel network in existing conductive hydrogels is weak, resulting in insufficient mechanical properties and cyclic stability, limiting its application in monitoring large-scale strain and long-term conductive stability.

Method used

Using carbon-based material-enhanced interpenetrating network conductive hydrogel preparation method, the pH value is adjusted and the heating reaction is carried out by adding silane coupling agent and silk protein to the carbon-based material solution, followed by ultrasonic dispersion and polymerization in the organic solution. , an interpenetrating structure consisting of the SF network and the hydrophobic PAM network is formed to enhance the interface interaction between the carbon-based material and the gel network.

Benefits of technology

The mechanical properties and cyclic stability of the conductive hydrogel are significantly improved, the tensile strain reaches 4960%, and excellent sensing performance is shown in monitoring the weak motion signals of the human body.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119385A_ABST
    Figure CN119119385A_ABST
Patent Text Reader

Abstract

The invention provides carbon-based material reinforced interpenetrating network conductive hydrogel as well as preparation and application thereof, and belongs to the field of flexible electronics and sensing materials. The method comprises the following steps: (1) preparing a carbon-based material organic dispersion liquid; and (2) preparing the interpenetrating network conductive hydrogel. The prepared interpenetrating network conductive hydrogel is composed of an SF network and a hydrophobicity-associated PAM network, a carbon-based material organic dispersion liquid is added into the SF network and the hydrophobicity-associated PAM network, so that the carbon-based material is uniformly dispersed in the gel network, the carbon-based material is easily mutually pulled with an SF molecular chain and a PAM molecular chain in the gel network to form electrostatic interaction and hydrogen bonds, and the conductivity of the hydrogel is improved. Meanwhile, the PAM molecular chain, the SF molecular chain and the carbon-based material have rich hydrophilic groups, so that a plurality of dynamic hydrogen bonds can be formed, and the interface interaction between the conductive material and a polymer matrix is greatly improved; the interpenetrating network conductive hydrogel prepared by the invention is used as a response thixotropic sensor and has excellent sensing performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of flexible electronics and sensor materials, and specifically relates to a carbon-based material-reinforced interpenetrating network conductive hydrogel and a preparation method and application thereof. Background Art

[0002] The continuous development of flexible electronic technology has promoted the in-depth research and exploration of soft robots, and also promoted the development of electronic skin, wearable sensors and other fields. However, currently flexible electronic materials are mainly inorganic materials such as metals and metal oxides, which cannot meet the requirements of conductivity and flexibility at the same time, resulting in poor contact between electronic devices and skin or tissue surfaces, and inaccurate signal acquisition. Conductive hydrogel combines the softness of hydrogel and the electronic properties of conductors, and has excellent mechanical properties and sensing properties, and is widely used in wearable devices and soft robots.

[0003] Conductive hydrogels combine the characteristics of hydrogels and conductive materials, with ultra-high sensitivity to pressure and strain, low detection limits, and excellent conductivity, making them the material of choice for designing flexible sensors. However, due to the weak interface between the gel network scaffold and the rigid conductive material, conductive hydrogels show mechanical properties with low stretchability (<1000%) and poor cyclic stability. In addition, in actual use, the conductivity will be greatly affected due to the accumulation or breakage of the conductive material during the cyclic deformation of the gel. These shortcomings severely limit the application of conductive hydrogels in monitoring large-scale strain and long-term conductive stability.

[0004] Therefore, how to strengthen the interfacial interaction between conductive materials and gel networks is crucial to the mechanical properties and cyclic stability of conductive hydrogels. Summary of the invention

[0005] The present invention aims to solve the technical problem that the interface interaction between the conductive material and the gel network in the existing conductive hydrogel is weak, and provides a carbon-based material-reinforced interpenetrating network conductive hydrogel and its preparation and application.

[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions: A method for preparing a carbon-based material-reinforced interpenetrating network conductive hydrogel comprises the following steps: (1) preparing a carbon-based material solution, adding a silane coupling agent thereto, mixing well, slowly dropping hydrochloric acid, adjusting the pH value of the solution to 3-9, heating the solution for reaction, and after the reaction is completed, centrifuging, washing, and drying the reaction product to obtain a pretreated carbon-based material; (2) adding the carbon-based material to the organic solution and uniformly dispersing it by ultrasonication to obtain an organic dispersion of the carbon-based material; (3) Prepare an acrylamide solution and add silk protein thereto, then add N,N-methylenebisacrylamide, ammonium persulfate, and a carbon-based material organic dispersion, stir evenly, and let stand at room temperature until the bubbles disappear; then polymerize at 60°C for 0.5 to 4 hours. After the reaction is completed, an interpenetrating network conductive hydrogel reinforced with a carbon-based material is obtained.

[0007] Furthermore, in step (1), the carbon-based material is graphene oxide, multi-walled carbon nanotubes, carbon black and Ti 3 C 2 T x One or more of the MXenes.

[0008] Furthermore, in step (1), the mass concentration of the carbon-based material solution is 0.3-13%, the volume is 5-15 mL, the silane coupling agent is KH560, and the volume of the silane coupling agent is 2-5 mL.

[0009] Furthermore, in step (1), the temperature of the heating reaction is 90-180° C., and the reaction time is 4-12 hours.

[0010] Furthermore, in step (2), the organic solution is one or more of ethylene glycol, N,N-dimethylformamide, acetone, ethanol, xylene, methyl acetate and cyclohexanone, and the ratio of the carbon-based material to the organic solution is 20-100 mg: 2-5 mL.

[0011] Furthermore, in step (3), the mass concentration of the acrylamide solution is 8 to 23%, and the volume is 5 to 15 mL.

[0012] Furthermore, in step (3), the usage ratio of the acrylamide solution, silk protein (SF), N,N-methylenebisacrylamide (MBA), ammonium persulfate (APS), sodium dodecylbenzene sulfonate (SDBS) and carbon-based material organic dispersion is 3g:0.2-1.5g:0.2mg:20mg:0.1g:2.5mL.

[0013] The present invention also provides a carbon-based material-reinforced interpenetrating network conductive hydrogel prepared by the preparation method of the carbon-based material-reinforced interpenetrating network conductive hydrogel.

[0014] The present invention also provides the use of the carbon-based material-reinforced interpenetrating network conductive hydrogel in the preparation of a piezoresistive response thixotropic sensor.

[0015] Compared with the prior art, the beneficial technical effects of the present invention are: 1. The carbon-based material-enhanced interpenetrating network conductive hydrogel prepared by the present invention is composed of an SF network and a hydrophobically associated PAM network, and an organic dispersion of the carbon-based material is added thereto so that the carbon-based material is evenly dispersed in the gel network. The carbon-based material is easily attracted to the SF molecular chains and the PAM molecular chains in the gel network to form electrostatic effects and hydrogen bonds. At the same time, there are abundant hydrophilic groups on the PAM molecular chains, the SF molecular chains and the carbon-based materials, which will form many dynamic hydrogen bonds, greatly improving the interfacial interaction between the conductive material and the polymer matrix.

[0016] 2. The present invention adds a surfactant sodium dodecylbenzene sulfonate (SDBS) to the prepolymer solution of the interpenetrating network conductive hydrogel, which can induce the SF random coil to form a β-sheet structure, thereby promoting the rapid molding of the gel; at the same time, under the initiator ammonium persulfate (APS) and heating conditions, acrylamide (AM) forms a PAM chain through free radical copolymerization, and the formed PAM molecular chain is interlaced with the original SF molecular chain, thereby improving the mechanical properties of the hydrogel, and the tensile strain can reach 4960%.

[0017] 3. The interpenetrating network conductive hydrogel prepared by the present invention is used as a responsive thixotropic sensor with excellent sensing performance. It can not only sense the change in the weight of the weight, but also monitor the weak movement signals of the human throat, muscles, heartbeat, etc. in real time. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 The present invention is a flow chart of the preparation of the interpenetrating network conductive hydrogel; Figure 2 To join Ti 3 C 2 T x Changes in the tensile properties of hydrogels before and after MXene material; Figure 3 is a stress-strain curve of the interpenetrating network conductive hydrogel of the present invention under 700% cyclic stretching; Figure 4 The graph is a change graph of the storage modulus and loss modulus of the interpenetrating network conductive hydrogel of the present invention in the temperature range of -50 to 60°C; Figure 5 This is a resistance signal change diagram of the interpenetrating network conductive hydrogel of the present invention when attached to a finger joint for sensing testing. DETAILED DESCRIPTION

[0019] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention. Example 1

[0020] Take 10mL of 0.3wt% Ti 3 C 2 T x MXene material solution, add 2mL silane coupling agent KH560, mix well and slowly add hydrochloric acid dropwise to adjust the pH value of the solution to 3-4; heat to 90℃ for heating reaction, after 4h of reaction, centrifuge, wash and dry the product to obtain pretreated Ti 3 C 2 T x MXene material; 20 mg Ti 3 C 2 T x The MXene material was added to 5 mL of ethylene glycol and dispersed evenly by ultrasonication to obtain Ti 3 C 2 T x MXene material organic dispersion.

[0021] Take 5 mL of 8 wt% acrylamide solution, add 1 g of silk protein to continue dissolving, and then add 0.2 mL of 0.1 wt% N,N-methylenebisacrylamide solution, 0.2 mL of 10 wt% ammonium persulfate solution, 1 g of sodium dodecylbenzene sulfonate and 5 mL of TiO2. 3 C 2 T x The organic dispersion of MXene material is stirred evenly and allowed to stand at room temperature until the bubbles disappear; then the polymerization reaction is carried out at 60°C for 0.5h. After the reaction is completed, an interpenetrating network conductive hydrogel is obtained.

[0022] like Figure 1 As shown, the interpenetrating network conductive hydrogel obtained in this embodiment has a physically cross-linked DN structure, which is composed of a SF network and a hydrophobically associated PAM network. Adding the surfactant sodium dodecylbenzene sulfonate (SDBS) to the prepolymer gel solution of the interpenetrating network conductive hydrogel can induce the SF random coil to form a β-sheet structure, thereby promoting the rapid formation of the gel. At the same time, under the initiator ammonium persulfate (APS) and heating conditions, acrylamide (AM) forms PAM chains through free radical copolymerization, and the formed PAM molecular chains are intertwined with the original SF molecular chains, thereby improving the mechanical properties of the hydrogel. In addition, adding Ti 3 C 2 T x MXene material organic dispersion to evenly distribute Ti in the gel network 3 C 2 T x MXene materials, Ti 3 C 2 T xThe MXene material is pulled together with the PAM molecular chains and SF molecular chains in the gel network, making the hydrogel have excellent tensile properties. 3 C 2 T x MXene materials are rich in hydrophilic groups, which will form many dynamic hydrogen bonds, thereby further improving the mechanical properties of interpenetrating network conductive hydrogels.

[0023] In order to explore Ti 3 C 2 T x The effect of MXene materials on the mechanical properties of hydrogels. Under the same experimental conditions, we prepared a group of 3 C 2 T x MXene hydrogels. Figure 2 As shown, without Ti 3 C 2 T x The tensile strain of the hydrogel of MXene material is 3595%, the tensile stress is 70kPa, and the addition of Ti 3 C 2 T x The tensile strain of the hydrogel of MXene material is 4960% and the tensile stress is 117 kPa. Example 2

[0024] Take 5mL of 13wt% carbon nanotube material solution, add 2mL of silane coupling agent KH560, mix well, and slowly add hydrochloric acid dropwise to adjust the pH value of the solution to 3-4; heat to 90°C for heating reaction, react for 4h, centrifuge, wash and dry the product to obtain pretreated carbon nanotube material; add 20mg of carbon nanotube material to 5mL of N,N-dimethylformamide, ultrasonically disperse evenly, and obtain an organic dispersion of carbon nanotube material.

[0025] Take 15mL of 23wt% acrylamide solution, add 1g of silk protein to continue dissolving, then add 0.2mL of 0.1wt% N,N-methylenebisacrylamide solution, 0.2mL of 10wt% ammonium persulfate solution, 1g of sodium dodecylbenzenesulfonate and 5mL of carbon nanotube material organic dispersion, stir evenly, and let stand at room temperature until the bubbles disappear; then polymerize at 60°C for 4h. After the reaction, an interpenetrating network conductive hydrogel is obtained.

[0026] Figure 2 The figure shows the stretching-unloading curve of the interpenetrating network conductive hydrogel prepared in this example under 700% strain. Figure 2It shows that its stress fluctuation is close to zero, proving that the interpenetrating network conductive hydrogel prepared in this embodiment has ultra-high tensile properties, and the hysteresis loop area of ​​its cyclic tensile curve is also significantly reduced. Therefore, its mechanical loss is relatively small, it has good elasticity, and can be used for multiple cycles under higher strain. Example 3

[0027] Take 10mL of 0.3wt% Ti 3 C 2 T x MXene material solution, add 2mL silane coupling agent KH560, mix well and slowly add hydrochloric acid dropwise to adjust the pH value of the solution to 3-4; heat to 90℃ for heating reaction, after 4h of reaction, centrifuge, wash and dry the product to obtain pretreated Ti 3 C 2 T x MXene material; 20 mg Ti 3 C 2 T x The MXene material was added to 5 mL of ethylene glycol and dispersed evenly by ultrasonication to obtain Ti 3 C 2 T x MXene material organic dispersion.

[0028] Take 5 mL of 8 wt% acrylamide solution, add 1 g of silk protein to continue dissolving, and then add 0.2 mL of 0.1 wt% N,N-methylenebisacrylamide solution, 0.2 mL of 10 wt% ammonium persulfate solution, 1 g of sodium dodecylbenzene sulfonate and 5 mL of TiO2. 3 C 2 T x The organic dispersion of MXene material is stirred evenly and allowed to stand at room temperature until the bubbles disappear; then the polymerization reaction is carried out at 60°C for 0.5h. After the reaction is completed, an interpenetrating network conductive hydrogel is obtained.

[0029] Figure 3 The graph shows the change of storage modulus (G¢) and loss modulus (G²) of the interpenetrating network conductive hydrogel of this embodiment in the temperature range of -50 to 60°C. Figure 3 In the figure, as the temperature decreases, the storage modulus and loss modulus of the PS network and the MPS network in the interpenetrating conductive hydrogel of this embodiment show an increasing trend. When the temperature drops to 10°C, the G¢ and G² of the PS network increase rapidly. This is because there is a large amount of water in the interpenetrating conductive hydrogel. When the temperature decreases, from a macroscopic point of view, it is a process of transformation from a gel state to a solid state, and the interpenetrating conductive hydrogel loses its elasticity.

[0030] Performance Testing The interpenetrating network conductive hydrogel prepared in Example 3 was cut into regular sheets (20 mm in length, 10 mm in width, and 8 mm in height), copper wires were connected on both sides and connected to an electrochemical workstation, a constant voltage was set to 1 mV, and it was pasted on the joint of the index finger. When a person bent his fingers at different angles, the resistance value of the interpenetrating network conductive hydrogel changed, thereby measuring the ability of the interpenetrating network conductive hydrogel to convert pressure signals into electrical signal outputs.

[0031] Figure 4 The figure shows the change of the resistance signal of the interpenetrating network conductive hydrogel when the finger is bent. When the finger is bent, the resistance value of the interpenetrating network conductive hydrogel increases with the increase of the bending angle, and the resistivity also increases accordingly. With the regular movement of the wrist, the resistance also shows regular changes accordingly.

Claims

1. A method for preparing a carbon-based material-reinforced interpenetrating network conductive hydrogel, characterized in that: The steps include: (1) Preparation of organic dispersion of carbon-based materials A carbon-based material solution is prepared, a silane coupling agent is added thereto, hydrochloric acid is slowly added dropwise after mixing evenly, the pH value of the solution is adjusted to 3-9, and a heating reaction is performed. After the reaction is completed, the reaction product is centrifuged, washed, and dried to obtain a pretreated carbon-based material; Adding the carbon-based material into the organic solution and uniformly dispersing it by ultrasonication to obtain an organic dispersion of the carbon-based material; (2) Preparation of interpenetrating network conductive hydrogel Prepare an acrylamide solution, add silk protein into it, then add N,N-methylenebisacrylamide, ammonium persulfate, and carbon-based material organic dispersion, stir evenly, and let stand at room temperature until the bubbles disappear; then polymerize at 60°C for 0.5 to 4 hours. After the reaction is completed, an interpenetrating network conductive hydrogel reinforced with carbon-based materials is obtained.

2. The preparation method according to claim 1, characterized in that: In step (1), the carbon-based material is graphene oxide, multi-walled carbon nanotubes, carbon black and Ti3C2T x One or more of the MXenes.

3. The preparation method according to claim 1, characterized in that: In step (1), the mass concentration of the carbon-based material solution is 0.3-13%, the volume is 5-15 mL, the silane coupling agent is KH560, and the volume of the silane coupling agent is 2-5 mL.

4. The preparation method according to claim 1, characterized in that: In step (1), the heating reaction temperature is 90 to 180° C., and the reaction time is 4 to 12 hours.

5. The preparation method according to claim 1, characterized in that: In step (1), the organic solution is one or more of ethylene glycol, N,N-dimethylformamide, acetone, ethanol, xylene, methyl acetate and cyclohexanone.

6. The preparation method according to claim 1, characterized in that: In step (2), the ratio of the carbon-based material to the organic solution is 20-100 mg: 2-5 mL.

7. The preparation method according to claim 1, characterized in that: In step (2), the mass concentration of the acrylamide solution is 8-23%, and the volume is 5-15 ml.

8. The preparation method according to claim 1, characterized in that: In step (2), the usage ratio of the acrylamide solution, silk protein, N,N-methylenebisacrylamide, ammonium persulfate, sodium dodecylbenzenesulfonate and carbon-based material organic dispersion is 3g:0.2-1.5g:0.2mg:20mg:0.1g:2.5mL.

9. Use of the interpenetrating network conductive hydrogel prepared by the method for preparing the carbon-based material reinforced interpenetrating network conductive hydrogel as claimed in any one of claims 1 to 8 in preparing a piezoresistive response thixotropic sensor.

Citation Information

Patent Citations

  • Carbon material composite gel as well as preparation method and application thereof

    CN113265084A

  • Silk fibroin / carbon material conductive hydrogel as well as preparation and application thereof

    CN113292744A

  • MPAE conductive composite hydrogel as well as preparation method and application thereof

    CN115232331A

  • Conductive dual-network hydrogel based on silk fibroin as well as preparation method and application of conductive dual-network hydrogel

    CN117024776A

  • Injectable nanocomposite silk hydrogel for targeted and controlled delivery of therapeutic agents

    IN201931004799A

Cited By

  • MXene and polyurethane synergistically modified micro-phase separation dual-network hydrogel as well as preparation method and application thereof

    CN121914500A

  • A microphase separation double network hydrogel synergistically modified by MXene and polyurethane, a preparation method and application thereof

    CN121914500B